The quantization of a Kerr-AdS black hole - Gerhardt, Claus (Advances in mathematical physics, 2018)
We apply our model of quantum gravity to a Kerr-AdS space-time of dimension , , where all rotational parameters are equal, resulting in a wave equation in a quantum space-time which has a sequence of solutions that can be expressed as a product of stationary and temporal eigenfunctions. The stationary eigenfunctions can be interpreted as radiation and the temporal ones as gravitational waves. The event horizon corresponds in the quantum model to a Cauchy hypersurface that can be crossed by causal curves in both directions such that the information paradox does not occur. We also prove that the Kerr-AdS space-time can be maximally extended by replacing in a generalized Boyer-Lindquist coordinate system the variable by such that the extended space-time has a timelike curvature singularity in .